Growth responses to fertilizer application of thinned, mid-rotation Pinus radiata stands across a soil water availability gradient in the Boland area of the Western Cape - Chikumbu, Vavariro (Stellenbosch : Stellenbosch University, 2011)
Thesis (MscFor)--Stellenbosch University, 2011.